Biofeedback, Humanistic Psychology and Psychosomatics in Family Practice - James, R. T. (1976)
An innovative educational approach to psychosomatic illness in family practice has been developed. It is a synthesis of experiential methods of non-verbal communication and creativity training developed from psychotronic applications of biofeedback, humanistic psychology and eidetics. The methodology, called eidetic biofeedback, operates on non-traditional models of human potential and involves a holistic approach to the mind-body/environment relationship. The methods work by transferring the responsibility for health back to the awareness of the individual. Of 200 office practice patients, 60 percent achieved major changes in personality integration and vitality. This was reflected in cessation of the presenting complaint, without symptom substitution and diminished demand for clinical services.